A comparative study on law governing invasion of privacy / Ahmad Faiz Razali... [ et al. ] - Razali, Ahmad Faiz; Faiz, Farhan Zafry; Johari, Joaina; Shaped, Khairul Ikhwan (Faculty of Law, 2013)
This paper looks into the protection towards privacy in Malaysia, specifically physical and territorial privacy. The scope of our research extends to all area of protection that could be attributable to privacy, which include Constitutional Law by virtue of Article 5 and Penal Code through Section 509. The inadequacies of protection granted by the said provisions are illustrated by way of case laws. Despite there is an implied recognition of the right to privacy, there is an inconsistency between judgment and the imposition of punishment. Further, in most cases, the punishment proves to be disproportionate to the humiliation suffered by the aggrieved party. In order for us to search for the best solution, extensive discussion and comparisons with the protection of other countries are provided in Chapter 3, which include countries like Singapore, Brazil, South Africa and England. This paper also discusses the relevance of the 2010 Personal Data Protection Act which has been purported to protect informational privacy, so as to determine whether it also applies to other forms of privacy. The final chapter provides a discussion on the most viable are of law to protect privacy, taking into account both civil and criminal protection. In light of the discussion, after balancing the pros and cons of both areas, we are able to say with certainty why criminalizing invasion of privacy is the best option. Apart from that, we simulate 2 provisions that should be incorporated into the Penal Code to solve the inadequacy.